Masculinity, alexithymia, and fear of intimacy as predictors of UK men's attitudes towards seeking professional psychological help. (30th January 2014) - Sullivan, Luke; Camic, Paul M.; Brown, June S. L.
<x xml:space="preserve">Abstract</x> Objectives Men's reluctance to access health care services has been under researched even though it has been identified as a potentially important predictor of poorer health outcomes amongst men. Male gender role socialization and male development may be important in accounting for men's underutilization of mental health services in the United Kingdom. Method A cross‐sectional online survey was used to administer standardized self‐report measures that were subject to regression analysis. Five hundred and eighty‐one men from the UK general population completed the survey, and 536 participants formed the final regression analysis. Results Men who score higher on measures of traditional masculine ideology, normative alexithymia, and fear of intimacy reported more negative attitudes towards seeking professional psychological help. Normative alexithymia fully mediated the effect of fear of intimacy on attitudes towards professional help seeking. In the final regression model, education significantly accounted for a proportion of unique variance in men's help‐seeking attitudes. Conclusions Hypothesized consequences of male emotional and interpersonal development and male gender role socialization were associated with men's attitudes towards seeking psychological help. These are important factors which could help to improve help seeking and mental health outcomes for men. Limitations of this study and implications for future research are discussed. <boxed-text content-type="box" id="bjhp12089-blkfxd-0010" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Men are less likely to seek help for physical and psychological problems and have poorer health outcomes across nearly all major illness and injury. Men's reluctance to access health care services is believed to be a major contributory factor to poorer health outcomes for men. What does the study add? The study is a large‐scale survey of UK men's attitudes towards professional psychological help seeking. Results provide evidence that hypothesized consequences of male gender role socialization and dominant masculine norms are associated with men's attitudes towards seeking professional psychological help. Attitudes towards psychological help seeking were associated with masculinity, alexithymia, and intimacy. Alexithymia fully mediated the effect of intimacy on men's attitudes towards psychological help seeking. Promoting help seeking in men could improve men's emotional well‐being and interpersonal functioning. </boxed-text>